The Determinants of Interest Rates Spread in Kenya - Nyansera, Ondari Cyrus; Mukras, Prof. M S; Momanyi, Dr. Gideon (International Journal of Economics, 2016)
Purpose: The main objective of the study was to analyze the determinants of interest rate spread in the Kenyan economy. Its specific objectives were to establish the bank specific factors macroeconomic factors and industry specific factors that influence the interest rate spread in Kenya. Methodology: This study analyzed the determinants of interest rate spreads in Kenya by focusing on eight banking institutions that significantly control deposits and loans market. The study used panel least squares estimation technique on annual data between years 2002 to 2011 to analyze the determinants of interest rates spreads as grouped in literature under: Bank-Specific Factors, Industry-specific data and Macroeconomic factors. The study was carried out using panel quantitative data analysis which involved the panel unit root test; Levin-Lin Chu and Im-Pesaran-Shin Tests and among other diagnostic tests including normality test, heteroscedasticity, Multicollinearity and Hausman tests. The study also used descriptive statistics such as mean, standard deviation. Due to the nature of the study STATA software was used to analyze the data. The analyzed data was then presented using figures, tables and graphs. Results: Among the bank specific factors the results revealed that non interest income, nonperforming loans and loan asset ratio were significant. In addition among the industry specific factors liquid asset ratio and loan asset ratio were significant. While the finding revealed that only Treasury bill was significant among the macroeconomic factors. These results imply that non interest income, nonperforming loans and loan asset ratio greatly affect interest rate spread negatively. While liquid asset ratio and loan asset ratio greatly contributes to the interest rate spread negatively. Unique contribution to theory, practice and policy: Several recommendation emanate from the study. Firstly, the high responsiveness of banks spreads to the proxy for the Treasury bill suggests that deregulation must eventually take place. Secondly, banks must continue to seriously deal with the issues of the high levels of non- performing loans and the diseconomies of scale in their operations. Thirdly, if there is to be any success in reducing banks' interest rate spreads to support long- term economic growth, the competitive environment in the banking system must be enhanced